2020
DOI: 10.1101/2020.02.10.940999
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Influence of species and processing parameters on recovery and content of brain tissue-derived extracellular vesicles

Abstract: Extracellular vesicles (EVs) are involved in a wide range of physiological and pathological processes by shuttling material out of and between cells. Tissue EVs may thus lend insights into disease mechanisms and also betray disease when released into easily accessed biological fluids.Since brain-derived EVs (bdEVs) and their cargo may serve as biomarkers of neurodegenerative diseases, we evaluated modifications to a published, rigorous protocol for separation of EVs from brain tissue and studied effects of pro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 69 publications
1
11
0
Order By: Relevance
“…In fact, the largest proportion of neural EVs will be cleared from the interstitial space by surrounding cells and never reach these body fluids. Recent efforts aimed at recovering neural EVs from the brain parenchyma starting with frozen human, macaque or mouse brain tissue (79)(80)(81)(82)(83). The basic idea is to dissociate the tissue under mild conditions with as few as possible damage to the cells and collect EVs present in the interstitial fluid.…”
Section: Biofluids and Tissue Isolationmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, the largest proportion of neural EVs will be cleared from the interstitial space by surrounding cells and never reach these body fluids. Recent efforts aimed at recovering neural EVs from the brain parenchyma starting with frozen human, macaque or mouse brain tissue (79)(80)(81)(82)(83). The basic idea is to dissociate the tissue under mild conditions with as few as possible damage to the cells and collect EVs present in the interstitial fluid.…”
Section: Biofluids and Tissue Isolationmentioning
confidence: 99%
“…The challenge is to minimize co-isolation of non-EV contaminants with the same physiochemical properties such as intracellular vesicles, intraluminal vesicles or membranous particles released from broken cells during tissue harvest, processing, or storing (79,84). Following gentle tissue disruption (mechanical procedures, enzymatic digestion), EV separation can be performed by ultracentrifugation (85), density-gradient ultracentrifugation (79)(80)(81)83), size exclusion chromatography (82,83), or precipitation (86). However, it is unavoidable that during brain dissociation artificial membrane fragments are generated from thin axons, dendrites (spines), synapses and myelin, which form small vesicles co-purifying with interstitial EVs.…”
Section: Biofluids and Tissue Isolationmentioning
confidence: 99%
See 1 more Smart Citation
“…The cochlea is surrounded by the otic vesicle that gradually ossi es and becomes rigid as the mouse ages, especially after P10, and this makes it di cult to dissect the basilar membrane for extracting cochlear tissue-derived sEVs. Some recent studies have used enzyme digestion for the purpose of maintaining the integrity of the cells as much as possible in order to extract EVs from fat, brain, and tumor tissues [35,[83][84][85][86], while other studies have ground the tissues as a necessary step for extracting EVs [85,[87][88][89]. Crescitelli et al showed that the digestive enzymes in the existing tissue extraction methods are ineffective for bone tissue, and the methods for this type of tissue need further optimization [90].…”
Section: Discussionmentioning
confidence: 99%
“…Although peripheral biofluid EV molecular profiles have been examined at the RNA and protein levels (Dutta et al, 2021; Jiang et al, 2021; Shi et al, 2014), how these findings compare with EVs present in the brain remains unclear. Brain-derived EVs (bdEVs) can be separated by gentle tissue digestion in a reproducible manner (Huang et al, 2020; Vella et al, 2017). Here, we separated and profiled bdEVs from PD, PSP, and control tissues.…”
Section: Introductionmentioning
confidence: 99%